1991
DOI: 10.2307/1242837
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Potential Contribution of Plant Breeding to Crop Yields: Flue‐Cured Tobacco, 1954–87

Abstract: Measurements are made of plant breeders' success in increasing potential flue‐cured tobacco yields from 1954 to 1987 in North Carolina. Nongenetic sources of yield increases are measured by the yield levels of a standard variety. New genetic material accounted for between 20% and 35% of yield increases on research station plots in the three tobacco‐growing regions. Recent genetic contributions have been small. The slowdown is not attributable to a federal tobacco policy shift in 1965 that slowed the growth in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 5 publications
0
40
0
Order By: Relevance
“…Perrin, Kuhnen, and Ihnens (1983) and Babcock and Foster (1991) were unable to detect a statistically significant shift in soybean and tobacco yields, respectively, when the Act passed, despite apparent increases in private soybean R&D spending and the dominance of the private sector in tobacco breeding. Carew and Devadoss (2003) detect a positive impact of Plant Breeders Rights on Canadian canola yields in some specifications, but this effect disappears when time fixed effects are included.…”
Section: Effectiveness Of Pbrsmentioning
confidence: 97%
“…Perrin, Kuhnen, and Ihnens (1983) and Babcock and Foster (1991) were unable to detect a statistically significant shift in soybean and tobacco yields, respectively, when the Act passed, despite apparent increases in private soybean R&D spending and the dominance of the private sector in tobacco breeding. Carew and Devadoss (2003) detect a positive impact of Plant Breeders Rights on Canadian canola yields in some specifications, but this effect disappears when time fixed effects are included.…”
Section: Effectiveness Of Pbrsmentioning
confidence: 97%
“…Babcock and Foster (1991) again used variety trial data (in this case from North Carolina) to examine the effect of PVP on tobacco variety releases and yields over the period 1954–1987. The study found no evidence that tobacco breeders increased their output in response to the PVP Act of 1970.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, we follow a variety trials data‐based comparison approach 9 . As Babcock and Foster (1991) note, measures of technical change from research station data can, at best, be interpreted as potential technical change. In addition, because the varietal trial data are not generated in response to the same economic incentives faced by growers, the response of grower yields to changes in input use cannot be measured from experimental trials.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a few studies that have assessed the impact of PVP in the US and Latin American countries (Perrin, Kunnings, and Ihnen, 1983;Butler and Marion, 1985;Kalton, Richardson, and Frey, 1989;Babcock and Foster, 1991;Jaffe and Van Wijk, 1995;Butler, 1996;Frey, 1996;Alston and Venner, 1998). There have been a few studies that have assessed the impact of PVP in the US and Latin American countries (Perrin, Kunnings, and Ihnen, 1983;Butler and Marion, 1985;Kalton, Richardson, and Frey, 1989;Babcock and Foster, 1991;Jaffe and Van Wijk, 1995;Butler, 1996;Frey, 1996;Alston and Venner, 1998).…”
Section: Plant Breeding Intellectual Property Rights and The Approprmentioning
confidence: 99%